Clonal Propagation Program for Eucalyptus globulus in Chile - Arnold, Roger; Carmona, Juan Carlos; Balocchi, Claudio (Bosque (Valdivia), 1991)
Eucalyptus globulus plantations are rapidly expanding in Chile, many pulp manufacturers are now keen to utilize up to 20% short fibered eucalypt timber in combination with long fibered radiata pine. Variability in unimproved E. globulus seedling plantations combined with heritability data reveal significant potential for genetic improvement in growth, form, and wood quality traits of this species. The genetic improvement program proposed by the 'Cooperativa de Mejoramiento Genético Universidad Austral de Chile-Corporación Nacional Forestal-Empresas Forestales' involves long term recurrent breedings with an initial concentration of resources on developing efficient clonal propagation systems. Clonal rooted cutting will enable optimization of gains from the breeding; a 40% increase in volume yield is estimated for clonal plantations compared to 20% for open pollinated seed orchard seedlings. Substantial gains in other traits, including stem for and wood quality are also considered by the program.